Graph classes a survey - Brandstädt, Andreas 1949-; Le, Van Bang 1959-; Spinrad, Jeremy P. (Society for Industrial and Applied Mathematics (SIAM, 3600 Market Street, Floor 6, Philadelphia, PA 19104), 1999)
This well-organized reference is a definitive encyclopedia for the literature on graph classes. It contains a survey of more than 200 classes of graphs, organized by types of properties used to define and characterize the classes, citing key theorems and literature references for each. The authors state results without proof, providing readers with easy access to far more key theorems than are commonly found in other mathematical texts. Interconnections between graph classes are also provided to make the book useful to a variety of readers
Mode of access: World Wide Web. - System requirements: Adobe Acrobat Reader
Includes bibliographical references (p. 251-292) and index
Preface -- 1. Basic concepts -- 2. Perfection, generalized perfection, and related concepts -- 3. Cycles, chords and bridges -- 4. Models and interactions -- 5. Vertex and edge orderings -- 6. Posets -- 7. Forbidden subgraphs -- 8. Hypergraphs and graphs -- 9. Matrices and polyhedra -- 10. Distance properties -- 11. Algebraic compositions and recursive definitions -- 12. Decompositions and cutsets -- 13. Threshold graphs and related concepts -- 14. The strong perfect graph conjecture -- Appendix A. Recognition -- Appendix B. Containment relationships -- Bibliography -- Index
Keywords: Graph theory; Graphentheorie